2020
DOI: 10.31234/osf.io/2gkht
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Home Advantage during the COVID-19 Pandemic in European football

Abstract: The home advantage (HA) is a robust phenomenon in soccer whereby the home team wins more games and scores more goals than the away team. One explanation is that the home crowd spurs on home team performance and causes the referee to unconsciously favour the home team. The Covid-19 pandemic provided a unique opportunity to assess this explanation for HA, as European soccer leagues played part of the 2019/2020 season with crowds present and concluded with crowds absent. Using multi-level modelling we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…This lack of diminishing of home advantage on rounds without an audience is contrary to McCarrick et al [ 11 ] and Tilp and Thaller [ 12 ].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This lack of diminishing of home advantage on rounds without an audience is contrary to McCarrick et al [ 11 ] and Tilp and Thaller [ 12 ].…”
Section: Discussioncontrasting
confidence: 62%
“…This suggests that crowd support is not a necessary precondition for the home advantage. More recently, McCarrick, Bilalic, Neave, and Wolfson [ 11 ] studied all European leagues that finished 2019–2020 season without an audience. Although no individual analysis by country was available, global results revealed that, with an audience, teams won on average 0.39 points per game more at home than away, a figure that diminished to only 0.22 points more at home than away without an audience.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the decrease in HA in soccer games without audience during the Covid-19 pandemic was confirmed by several working papers applying regression models. Home performance, assessed as home wins, point differences between home and away team, or team dominance decreased in the collapsed data from 13 European leagues (McCarrick et al, 2020 ) and in the first German Bundesliga (Fischer and Haucap, 2020 ). Interestingly, Fischer and Haucap ( 2020 ) did not observe a reduction in home advantage in the second and third German soccer league.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer and Haucap ( 2020 ) analyzed the first three divisions of the German Bundesliga and observed a reduction of the HA only in the first league which was related to occupancy rates, i.e., HA was reduced most in teams with high occupancy in their stadium during regular seasons. McCarrick et al ( 2020 ) analyzed the effect of games without audience collapsed from 15 different European soccer leagues and found that empty stadiums decreased home team performance and affected referees' decisions. When analyzing 23 leagues worldwide, Bryson et al ( 2020 ) discovered large and statistically significant effects on the number of yellow cards when no audience was present.…”
Section: Introductionmentioning
confidence: 99%
“…Following the restrictions that were implemented globally to combat the COVID-19 pandemic, spectators were prohibited from attending the matches played toward the end of 2019/2020 season. The absence of the spectators enabled researchers to study the effect of the crowd on the home field advantage in professional soccer across leagues and countries (e.g., Bryson et al, 2020;Cueva, 2020;Deutscher et al, 2020;Dilger and Vischer, 2020;Ferraresi and Gucciardi, 2020;Fischer and Haucap, 2020;Leitner and Richlan, 2020;McCarrick et al, 2020;Reade et al, 2020;Scoppa, 2020;Sors et al, 2020;Tilp and Thaller, 2020). There seems to be overall consensus that the absence of the crowd has a particularly strong effect in the German 1 Note that the same audience that is perceived as facilitative/supportive by the home team may be perceived as inhibitive/threatening by the away team.…”
Section: Introductionmentioning
confidence: 99%